THE INFLUENCE OF THE USE OF WEBSITE MEDIA IN CREASING ADOLESCENTS KNOWLEDGE ABOUT THALASSEMIA AT SMAN 1 SINGAPARNA - Maulana, Heri Djamiatul (Universitas Aisyah Pringsewu, 2024)
Background: Thalassemia is the most common global health problem in the world. Until now,the number of thalassemia sufferers is increasing. One way to prevent thalascemia is to provide education in areas that may experience thalasemia.Research Objective: To determine the influence of the use of website media in increasing adolescents knowledge about thalassemia at SMAN 1 Singaparna,Tasikmalaya Regency.Method: Using quantitative research with a quasy experimental research design with a pre-test post-test with control group design. The sampling technique used is a purposive sampling technique,namely simple random sampling with a sample of 68 people.Results: An average score was obtained before treatment in the intervention group of 72.65 and after treatment was given 92.65. Meanwhile,the control group obtained an average score of 74.41 before treatment and 80.88 after treatment. The intervention group had a higher difference of 20.00 compared to the control group of 6.47. Based on the results of the paired sample t-test in both groups,the same value was obtained with a p value of 0.0000.05, then Ho was rejected and Ha was accepted.Conclusion: There is an effect of the use of website media on increasing adolescents knowledge about thalassemia at SMAN 1 Singaparna, Tasikmalaya Regency.Suggestion: It is hoped that the next researcher can develop this research using other online media.